Association between patient‐reported hearing and visual impairments and functional, psychological, and cognitive status among older adults with cancer. Issue 15 (24th May 2018) - Soto‐Perez‐de‐Celis, Enrique; Sun, Can‐Lan; Tew, William P.; Mohile, Supriya Gupta; Gajra, Ajeet; Klepin, Heidi D.; Owusu, Cynthia; Gross, Cary Philip; Muss, Hyman B.; Lichtman, Stuart M.; Chapman, Andrew E.; Cohen, Harvey Jay; et al.
Abstract : BACKGROUND: Hearing and visual impairments are common among community‐dwelling older adults, and are associated with psychological, functional, and cognitive deficits. However, to the authors' knowledge, little is known regarding their prevalence among older patients with cancer. METHODS: The current study was a secondary analysis combining 2 prospective cohorts of adults aged ≥65 years with solid tumors who were receiving chemotherapy. The authors assessed the association between patient‐reported hearing and/or visual impairment (defined as fair/poor grading by self‐report) and physical function, instrumental activities of daily living (IADLs), anxiety, depression, and cognition. Descriptive analyses were conducted to summarize patient and treatment characteristics. One‐way analysis of variance and chi‐square tests were conducted as appropriate to examine differences between patients with and without sensory impairments. Logistic regression was used to analyze associations between sensory impairments and outcomes. RESULTS: Among 750 patients with a median age of 72 years who had solid tumors (29% with breast/gynecological tumors, 28% with lung tumors, and 27% with gastrointestinal tumors), approximately 18% reported hearing impairment alone, 11% reported visual impairment alone, and 7% reported dual sensory impairment. Hearing impairment was associated with IADL dependence (odds ratio [OR], 1.9), depression (OR, 1.6), and anxiety (OR, 1.6). Visual impairment was associated with IADL dependence (OR, 1.9), poor physical function (OR, 1.9), and depression (OR, 2.5). Dual impairment was associated with IADL dependence (OR, 2.8), anxiety (OR, 2.3), depression (OR, 2.5), and cognitive impairment (OR, 3.2). CONCLUSIONS: Sensory impairment is common among older adults with cancer. Patients with sensory impairment are more likely to have functional, psychological, and cognitive deficits. Interventions aimed at improving the vision and hearing of older adults with cancer should be studied. Cancer 2018 . © 2018 American Cancer Society . Abstract : Among older adults with solid tumors, greater than one‐third report visual or hearing impairment, and 7% report both. Older patients with cancer and sensory impairments are more likely to have functional, psychological, and cognitive deficits.